Efeitos do Programa Nacional de Alimentação Escolar (PNAE) sobre a agricultura familiar e desempenho escolar - Ipolito, Antonia Leudiane Mariano (2023)
The National Program for the Strengthening of Family Farming (PNAE) is a public policy of wide relevance, which contributes to the students' nutrition, assisting in their growth and biopsychosocial development, and, among its objectives, there is also the encouragement of family farming. This produces, approximately, a third of the world's food, evidencing an important role for universal feeding, as expressed in the FAO document (2021). Under these circumstances, policies to encourage and ensure the production, minimum income, and marketing of these farmers' products are necessary instruments to ensure food and nutritional sovereignty and security for society. The reformulation of PNAE, through Law 11.947, of 2009, represents this advance, supported by which it was determined that 30% of the resources intended for the purchase of school food, passed on by the National Fund for Education Development (FNDE) to PNAE, must be used for the purchase of food from family farming, providing a connection between school meals and family farming. In view of the importance of the program, this study is structured in two chapters, reporting on both main themes, according to the objectives of PNAE, which are the direct effect on family farming and on the performance and school performance of students enrolled in rural schools. To meet this desideratum, a discontinuous regression design (RDD) approach was adopted to estimate the influence on variables related to the objective of this study, considering the groups of municipalities that meet the minimum percentage of 30% vis-à-vis those that fall short of this percentage. In the first chapter, the results for Brazil show a positive impact on the income of family farming establishments. The analysis for the regions, however, points out that there are still weaknesses to be addressed in order to expand the effects arising from the PNAE. In the other chapter segment, the analysis for Brazil showed that PNAE has an effect on the performance of rural schools. As for the regions, an effect was obtained only for the Northeast and South, specifically on the rate of school performance (dropout). Overall, the evidence highlights the fact that policies such as PNAE have great importance, connecting family farming and school feeding.